Uncovering Disney’s Pedagogy of Classism in Their “Reality” Programming - Robin Redmon Wright (Adult Education Research Conference, 2016)
Disney now saturates cable television with programs like Duck Dynasty, Swamp People, Lady Hoggers, and Appalachian Outlaws. These shows are actively promoting cultural myths that reinforce the neoliberal agenda that oppressed many adults with which we work. Our responsibility, then, is to expose those messages for what they are.
Keywords: Disney; classism; adult identity